(3ELGRI dedG oeUWbaj Hf eMeO aj GdWQjbs - (3TjN oeUWais; (3GdeQGHW , eMeO Hf eMeO Hf YHO GdYRjR GdeQGHW GdSLdeGSj, CHh YHO Gddg,J (B1140 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CT b UOhQ GdUOjbjf HYgO GdejKGb Ef Chd eG CaJJM Hg cJGH Gddg GdeLjO MeO ef bQH ChdjGAg Edi MVQI CfSg s
(3BNQgG (B:s
(3hEPG bjd dc (B: (3Ci TF efgG Mj hCj TF efgG ejJ ? abd Mjf Jba JehRJ hMjf JeTj JMjG hGddg CYde HGdUhGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B234s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B13 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs